Subjective Theories of Chinese Office Workers With Irregular Physical Activity: An Interview-Based Study - Shang, Borui; Duan, Yanping; Brehm, Walter; Liang, Wei (Frontiers in Psychology, 2022)
Abstract Objectives: Individuals with irregular PA participation are defined as fluctuators. This study aimed to comprehend how fluctuators’ perceived barriers and motivators in their subjective theories are exhibited and cognitively represented in relation to their everyday PA practices and lapses. Methods: The design of "Research Program Subjective Theories" was used to explore and present fluctuators' cognition concerning PA participation. 30 fluctuators were invited to semi-structured interview. By inductive and deductive coding, fluctuators' verbal data were converted into word categories for extracting commonalities and comparing differences. By remaining word categories of high frequency and exploring the interrelationships among the remained word categories using statistical analyses, a superstructure (i.e. visualized representation of fluctuators' overall cognition) including fluctuators' main PA motivators, barriers, and behavioral outcomes was compiled. Results: Fluctuators face common motivators as barriers such as lack of time, lack of willpower, lack of social support, and physical reasons (discomfort, injuries, or diseases). Fluctuators' subjective theories primarily differed in motivational configurations. The physically motivated fluctuators (i.e. those predominantly motivated by physically related motivators) were more linked with low PA level, while the mixed motivated fluctuators (i.e. motivated by both physically related and emotionally or socially related motivators) were more likely associated with moderate PA level. Exemplars of the three typical fluctuators were also demonstrated to reveal their real experiences and situations in the daily life context. Conclusion: Due to the fact that fluctuation research is still in its infancy, this study represents a significant chance to promote knowledge growth on this area. Future studies are recommended to convert findings from the present study into interventions that benefit fluctuators in overcoming perceived barriers and enhancing motivations to eventually participate in regular PA.